2014
DOI: 10.1186/1471-2458-14-1095
|View full text |Cite
|
Sign up to set email alerts
|

National indicators of health literacy: ability to understand health information and to engage actively with healthcare providers - a population-based survey among Danish adults

Abstract: BackgroundHealth literacy is a multidimensional concept covering a range of cognitive and social skills necessary for participation in health care. Knowledge of health literacy levels in general populations and how health literacy levels impacts on social health inequity is lacking. The primary aim of this study was to perform a population-based assessment of dimensions of health literacy related to understanding health information and to engaging with healthcare providers. Secondly, the aim was to examine ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 34 publications
14
159
2
8
Order By: Relevance
“…Older people may be more likely to accept interventions related to maintaining independence and “being the best you can be” more readily (Barker et al, ). Attention also needs to be paid to the level of understanding that PAV clients have about their risk of falling and the role different healthcare providers’ play in falls prevention (Bo, Friis, Osborne, & Maindal, ). This may be related to the older person's level of health literacy and is an area that warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Older people may be more likely to accept interventions related to maintaining independence and “being the best you can be” more readily (Barker et al, ). Attention also needs to be paid to the level of understanding that PAV clients have about their risk of falling and the role different healthcare providers’ play in falls prevention (Bo, Friis, Osborne, & Maindal, ). This may be related to the older person's level of health literacy and is an area that warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Aber auch die NRW-Studie findet keine signifikante Assoziation zwischen allgemeiner GK und Alter [10]. Somit zeigt die soziodemografische Verteilung der GK-Level in GEDA 2013s ein gemischtes Bild, wie es in anderen bevölkerungsweiten Studien zu finden ist [15,34,35]. Hinsichtlich der Bildungsunterschiede wird vermutet, dass GK eine Rolle bei der Erklärung des Zusammenhangs zwischen niedrigem Bildungsniveau und schlechter Gesundheit spielen könnte [36].…”
Section: Vergleich Mit Anderen Studienunclassified
“…Bo et al. () found that when all other factors were adjusted, people who were living alone had lower health literacy scores compared to those who lived with others. Although the effect size was considered small, another study found that living alone was associated with lower scores in social support for health (Beauchamp et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In the Danish study, those whose mother tongue was not Danish scored lower levels of health literacy (Bo et al., ). In the Australian study, participants for whom English was not their first language scored lower on scales focused on relationships with health professionals, navigation of the healthcare system, and finding or understanding health information (Beauchamp et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation